Integrating Qur’anic verses in teaching Arabic rhetoric (balaghah): A classroom action research approach - Aida, Izzah Nur; Maulana, Asep; Rosid, Abdur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The Qur’an exemplifies extraordinary rhetorical excellence, particularly through its application of balaghah (Arabic rhetoric), including features such as tasybih (simile) that demonstrate its linguistic inimitability. However, traditional Islamic education often relies heavily on classical Arabic poetry to teach balaghah, which may present challenges for intermediate learners. This study aims to enhance students’ comprehension and engagement in balaghah by integrating familiar and spiritually resonant Qur’anic verses into instruction. Employing a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, the study was conducted over two cycles with Grade II Wustho students at Madrasah Diniyah Unggulan Bustanul Ulum Mlokorejo. Data were collected through pre- and post-tests, interviews, document analysis, and classroom observation. Results revealed notable improvements in student achievement, with average scores increasing from 56.75 (pre-cycle) to 72.3 (Cycle I) and 77.6 (Cycle II). The percentage of students achieving basic competency rose from 40% to 80%. In addition, students exhibited deeper contextual understanding and improved ability to identify key rhetorical elements such as musyabbah, musyabbah bih, and wajh syibh. This research underscores the pedagogical value of integrating Qur’anic content in rhetoric instruction, offering a contextually relevant and spiritually meaningful strategy to enrich Arabic language education.